(untitled) (Third Sector Social Economic Review, 2025)
This study examines the impact of crime rates, insecurity perception, and religiosity on citizens’ trust in public institutions in Türkiye. Trust in government is essential for social cohesion and the effective operation of administrative systems. However, increasing crime rates and a heightened sense of insecurity contribute to a decline in public confidence in state institutions, potentially weakening the social contract. Using data from the World Values Survey Wave 7, this research investigates the relationship between crime, insecurity, and trust, while also assessing the moderating role of religiosity. Findings indicate that higher crime rates and insecurity negatively affect trust in public institutions. However, religiosity presents a complex relationship, where individuals who engage in religious practices exhibit lower trust, while self-identified religious individuals show greater confidence in public institutions. Based on empirical findings specific to the Turkish context, this study identifies areas where public trust in the government and public administration has weakened, demonstrating that such a decline may adversely affect the effectiveness and legitimacy of public policies. The findings highlight the critical importance of strengthening transparency, accountability, and participatory mechanisms in the process of rebuilding public trust. In this regard, the study underscores the need to reconsider the current governance approach and adopt more inclusive and effective strategies.